The clinical efficiency of lycium-rehmannia pills in treating dry eye symptom: A meta-analysis. Issue 28 (10th July 2020) - Lou, Lili; Fu, Hongling; Liu, Hanmin
Abstract: Background: Dry eye symptom threatens human health and causes a larger burden of disease, the study aims to systematically compare the therapeutic effect of Lycium-rehmannia pills combined with topical eye drops and pure western medicine (western medicine eye drops) on dry eye symptom, to provide a reflection and enlightenment for clinical treatment. Method: PubMed, The Cochrane Library, EMbase, MEDLINE, CBM, WanFang, VIP, and CNKI databases were searched manually and automatically by the computer until March 2019 and relevant randomized controlled trials (RCTs) were selected. Article selection and data extraction were conducted by 2 researchers independently, then RevMan 5.3 was applied for meta-analysis. Result: Fifteen randomized controlled trials were included, including 1222 patients (eyes = 2382). The meta-analysis results showed that Lycium-rehmannia pills combined with western medicine were superior to the control group in terms of therapeutic efficiency [OR = 4.38, 95% confidence interval (CI) (3.26, 5.89), P  < .00001]. There were controversial results that the study group was better than the control group in Basic Schirmer test [MD, 2.46, 95% CI (1.49, 3.44), P  < .00001], tear break up time [MD, 3.79, 95% CI (3.57, 4.01), P  < .00001], and Fluorescein test [MD, −1.29, 95% CI (−1.42, −1.15), P  < .00001], but Lycium-rehmannia pills combined with western medicine could not reduce the incidence of adverse reactions, including eyelid inflammation [OR = 1.00, 95% CI (0.37, 2.72), P  = 1.00] and congestion symptom [OR = 0.55, 95% CI (0.18, 1.65), P  = .28]. Conclusion: Lycium-rehmannia pills combined with western medicine is better than the control group of therapeutic efficiency in the treatment of dry eye symptom. Due to the quantity and quality limitations of the literature, there were controversial results that the study group was better than the control group in Basic Schirmer test, Tear break up time, Fluorescein test, and reduced adverse reactions, including inflammation of the eyelids and congestion. The above conclusion needs more clinical trials to test and verify.